Chemical and oxidative changes of ultra-processed oils by potato fries in the central ambulant commerce (Research, Society and Development, 2020)
The objective of this work is to evaluate the oxidative characteristics of the oils of fries of potatoes obtained from the street commerce of Teresina, Piauí, Brazil. Aiming to determine the oleochemical parameters of Acidity Index, Free Fatty Acid Index, Peroxide Index; Iodine index and 2-thiobarbituric acid test. Five batches of potato fries were collected at different locations. 96 samples of coconut and soy oils were analyzed from five commercial establishments in Teresina, Piauí, 66 of which were destined for oleochemical analysis and 12 for the 2-thiobarbituric acid test. The analyzes of oleochemical parameters were carried out according to the American Oil Chemists' Society, while the oxidative analyzes, by the same method, at the Federal Institute of Education, Sciences and Technology of Piauí, Campus Teresina-Central. As a result, the acidity index analysis showed values in accordance with international legislation for fried oils. The percentages of free fatty acids and peroxide index were within the limits established for fried oil in relation to the legislation. The results of the iodine index showed greater unsaturation in the lipid chains in lots two and three. The 2-thiobarbituric acid test showed oxidative changes in batches four and five. It was concluded that oxidative processes were evidenced in all oil samples, especially coconut oil, which showed better oxidation stability in relation to soybean.